2022
DOI: 10.1109/access.2022.3146128
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Achievement Goal Orientation, Learning Strategies, and Digital Skill on Engineering Skill Self-Efficacy in Thailand

Abstract: Rapid technological changes in industry and institutions of higher education required that their continuous learning and teaching methods conform to the needs of the labor market in the digital era. Building the engineering skill self-efficacy of students should be a key goal for educational institutions as they develop necessary skills for future engineers. This work investigated structural factors influencing engineering skill self-efficacy by conducting a questionnaire survey among 1,316 engineering student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…It proposed that teachers still need enhanced skills in teaching digitally [55][56][57]. Some studies also confirmed that self-efficacy and attitudes have some influence on digital competence [58,59]; teachers who perceive themselves as having insufficient self-efficacy or attitudes often show low self-confidence that impacts their digital competence to provide learning opportunities for their students [60,61]. Fewer studies of digital competence are related to gender and age [62,63].…”
Section: Teachers' Digital Competencementioning
confidence: 99%
See 1 more Smart Citation
“…It proposed that teachers still need enhanced skills in teaching digitally [55][56][57]. Some studies also confirmed that self-efficacy and attitudes have some influence on digital competence [58,59]; teachers who perceive themselves as having insufficient self-efficacy or attitudes often show low self-confidence that impacts their digital competence to provide learning opportunities for their students [60,61]. Fewer studies of digital competence are related to gender and age [62,63].…”
Section: Teachers' Digital Competencementioning
confidence: 99%
“…The more digitally competent teachers are, the better they are at the use of digital tools and the integration of information technology [52][53][54][55][56]. Therefore, schools or policymakers still need to formulate reasonable policies to encourage teachers to improve their digital capabilities, actively participate in digital technology training, improve teachers' attitudes and self-efficacy in using digital technology, and promote the learning of their digital capabilities, to apply ICT to classroom teaching and improve the quality of teachers' teaching [60][61][62][63][64]. Furthermore, the results confirm teachers' digital tools use has a positive and significant effect on ICT integration [71,72].…”
Section: Plos Onementioning
confidence: 99%
“…Fourth, causal attributions play a determining role in academic achievement since they determine the ability of students to maintain the effort and persevere in their goals [84][85][86][87][88][89][90][91]. In this way, those students who have come to create an attributional style based on helplessness and characterized by the belief that their effort has little or no value for achieving positive academic outcomes are not proactive in the tasks, and the probabilities of dropping out are much higher [92][93][94][95][96], especially when the level of demand begins to increase given the natural evolution of the academic year.…”
Section: Key Variablesmentioning
confidence: 99%
“…In this way, highly motivated students, with an optimal level of self-efficacy, positive emotions based on the belief in their own ability, and an adaptive attributional pattern, consider that luck is not a particularly determining factor in their academic development and trust. Their attitude can make a difference and make it possible to achieve success [91,[108][109][110][111]. For these reasons, they are capable of maintaining effort and perseverance until reaching their academic goals, radically decreasing the probability of falling into hopelessness embedded in university dropout.…”
Section: Key Variablesmentioning
confidence: 99%
“…Thus, information communication technology (ICT), digital technology, social media, and social networking currently play important roles in establishing the effective coexistence of distance and education management [11,12]. In addition, these online technologies are applied to the processes of teacher production [13][14][15].…”
Section: Introductionmentioning
confidence: 99%